Immunohistochemical Profile of Nonfunctioning Pituitary Adenomas - Solovey, Mariana (J Endocr Soc, 2021)
Background: Nonfunctioning pituitary adenomas (NFPAs) are neuro-endocrine tumors without clinical and laboratory signs of anterior pituitary hormonal hypersecretion. The recent World Health Organization classification is based on the adenohypophyseal cell lineages and requires immunohistochemical evaluation of adenohypophyseal hormones and pituitary transcription factors. There are few data regarding the age and sex prevalence of different cell-types nonfunctioning adenomas and clinical data correlations. Objective: To discover the immunohistochemical profile of large cohort of NFPAs. Materials and Methods: The study includes 100 consecutive cases of endoscopically transsphenoidally removed nonfunctional pituitary adenomas, immunohistochemically assessed for anterior pituitary hormones and transcription factors. Clinical presentation, imaging, laboratory hormonal data and immunohistochemical staining features have been analyzed. All patients (64 women and 36 men) have been divided into four age groups: 20-34 (A) years old, 35-44 (B) years old, 45-59 (C) years old, 60-70 (D) years old. Peculiarities of immunohistochemical profile have been statistically analyzed in those age groups. Results: Most tumors (97%) were macroadenomas with mass effect symptoms. In the groups of silent corticotroph and Pit-1 adenomas most of the patients had subclinical symptoms of hormonal hypersecretion. The proportions of silent gonadotroph adenomas have appeared to be increased with age with predominant prevalence in group D (60%) in women and group C (78, 6%) in men. The proportions of silent Pit-1 adenomas decreased with age with maximum rate in group A (77,8%) in women and in group A (50%) in men. The incidence of silent corticotroph adenomas was different: increasing with age in women with maximum (36,8%) in group C and decreasing from young age (30%-0%) in men age groups B-D respectively. Plurihormonal pituitary adenomas from different cell lineages were found only in women, with maximum incidence rate (17,6%) in group B. The incidence of “null cell” adenomas didn’t differ in men and women in group B and C but was much more higher in men in groups A and D (16,7% vs 0% and 33% vs 6,6% respectively). Conclusions: The different age and sex prevalence of NFPAs, revealed in our study, may be helpful in diagnosing and optimal treatment of NFPAs.